A novel strain-based bone-fracture healing algorithm is able to predict a range of healing outcomes - Morgan, George T.; Low, Lucas; Ramasamy, Arul; Masouros, Spyros D. (Frontiers in Bioengineering and Biotechnology, 2024)
Fracture healing is a complex process which sometimes results in non-unions, leading to prolonged disability and high morbidity. Traditional methods of optimizing fracture treatments, such as in vitro benchtop testing and in vivo randomized controlled trials, face limitations, particularly in evaluating the entire healing process. This study introduces a novel, strain-based fracture-healing algorithm designed to predict a wide range of healing outcomes, including both successful unions and non-unions. The algorithm uses principal strains as mechanical stimuli to simulate fracture healing in response to local mechanical environments within the callus region. The model demonstrates good agreement with experimental data from ovine metatarsal osteotomies across six fracture cases with varying gap widths and inter-fragmentary strains, replicates physiological bony growth patterns, and is independent of the initial callus geometry. This computational approach provides a framework for developing new fracture-fixation devices, aid in pre-surgical planning, and optimize rehabilitation strategies.